Ecological Responsiveness and Corporate Real Estate. (March 2016) - Eichholtz, Piet M. A.; Kok, Nils; Quigley, John M.
Firms' real estate choices significantly affect their sustainability, due to real estate's impact on the natural environment. This paper investigates the ecological responsiveness of firms in specific industries by analyzing the decisions these firms make in occupying office space. We analyze the decisions of more than 11, 000 tenants to choose office space in green buildings or in, otherwise comparable, conventional buildings nearby. Controlling for building quality and location, we find that corporations in the oil and banking industries, as well as non-profit organizations, are among the most prominent green tenants. Furthermore, measures of an industry's human capital intensity are positively related to the propensity to lease green office space. These empirical findings confirm the theoretical framework on economic advantage and institutional pressure as important determinants for the ecological responsiveness of firms.